(untitled) (Research, Society and Development, 2021)
The objectives of this study were to know the feelings of nurses regarding the care of patients in an attempt of self-extermination, together to describe the role of nurses in care, to verify the possibilities that these feelings may cause some kind of psychological disorder in nurses and to understand the reality of the nurse’s routine in the first assistance in urgency and emergency to patients in self-extermination attempt. For this study to be carried out, there was the participation of five nurses who work on shifts in the urgency and emergency service (Emergency Room), through the analysis of the Collective Subject Discourse (CSD), then answered questions that facilitated the understanding of the facts discussed. In agreement with the results obtained in the research, we can observe that nursing care in urgent and emergency care is extremely important to reduce deaths and self-extermination attempts. Appropriate reception facilitates the collection of information, thus facilitating care for this patient. In agreement with the results obtained in the research, we can observe that nursing care in urgent and emergency care is extremely important to reduce deaths and self-extermination attempts. Appropriate reception facilitates the collection of information, thus facilitating care for this patient.